Emptiness in Tragic Times: some remarks on today´s Brazilian public policies - Garnica, Antonio Vicente Marafioti [UNESP] (FapUNIFESP (SciELO), 2022)
This paper has a hybrid structure and is, at the same time, an academic essay, a manifesto and a summary of articles published in the mainstreammedia. It was composed, mainly, from journalistic sources, and has as its theme the current Brazilian public policies. To argue about the absence of these public policies today, the article presents a summary of situations that characterize the Bolsonaro Administration and ends with some brief remarks on public policies in Mathematics Education, particularly those related to Distance Education.
O Vazio em Tempos Trágicos: notas sobre políticas públicas no Brasil atual
Keywords: Bolsonaro Administration; E-learning; Public Policies